2016
DOI: 10.1111/1754-9485.12478
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic reference levels for common paediatric fluoroscopic examinations performed at a dedicated paediatric Australian hospital

Abstract: Introduction: Diagnostic reference levels (DRL) of procedures involving ionising radiation are important tools for optimising radiation doses delivered to patients and to identify cases where the levels of dose are unusually high. This is particularly important for paediatric patients undergoing fluoroscopic examinations as these examinations can be associated with a high radiation dose. In this study, a large amount of paediatric fluoroscopic data has been analysed to: 1 establish local DRL, 2 identify the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…The paediatric patient dose data analysed here are from the examinations performed at the Women's and Children's Hospital (WCH) in Adelaide. In particular, computed tomography (CT), fluoroscopy and nuclear medicine examinations are from these modality's databases. Minimum, maximum and average effective doses have been calculated for CT, fluoroscopic, general radiographic and nuclear medicine examinations in the age groups 0 to <5 years, 5 to <10 years, 10 to <15 years and 15 to <18 years.…”
Section: Methodsmentioning
confidence: 99%
“…The paediatric patient dose data analysed here are from the examinations performed at the Women's and Children's Hospital (WCH) in Adelaide. In particular, computed tomography (CT), fluoroscopy and nuclear medicine examinations are from these modality's databases. Minimum, maximum and average effective doses have been calculated for CT, fluoroscopic, general radiographic and nuclear medicine examinations in the age groups 0 to <5 years, 5 to <10 years, 10 to <15 years and 15 to <18 years.…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that screening time is a poor indicator of dose. It does not correlate with DAP and Bibbo et al . have confirmed this.…”
mentioning
confidence: 92%
“…The study by Bibbo et al . in this issue is recommended reading for radiologists performing fluoroscopy and/or angiography.…”
mentioning
confidence: 99%
See 2 more Smart Citations